Efektifitas buku English for Specific Purpose pada kemampuan membaca mahasiswa biologi - luluk choirun nisak nur (Universitas KH. A. Wahab Hasbullah, 2020)
This research is categorized as quasi experimental research. This research intent to know the effectiveness of using English for Specific Purpose (ESP) textbook especially on student’s reading skill. This experimental research was held at KH. A. Wahab Hasbullah University on Biology Program. The subject of this research is the first semester of biology program. The population is all students of biology program. A random sampling used for the subject of the study, that was A and B class which contain 20 students in each class. Class A was as experimental class and calss B was as control class. The data for this research was scored of the pretest and posttest, and they were compared and analyzed by using analysis of ANCOVA. Based on the ancova analysis, the F-Ratio 39,71 while the critical F-critical 4,04. This is significant at the level 0.05, so that the null hypothesis is rejected and the alternative hypothesis is accepted. In other words, there is a significant difference on Reading skill between students taught by using ESP textbook than those taught without ESP textbook. It can be concluded there is significant different of using ESP textbook especially on reading skill. Finally, the researcher suggested that the lecturer should used ESP textbook as one of teaching English for Biology, because this book provides some reading text contain of biology material. So that the students can be focused on their scope of biology, learning biology while in English.